Mechanical Properties of Single‐Layer Diamond Reinforced Poly(vinyl alcohol) Nanocomposites through Atomistic Simulation. Issue 10 (8th July 2021) - Li, Chengkai; Zhang, Zheyi; Zhan, Haifei; Zheng, Zhuoqun; Bai, Jingshuai; Gu, Yuantong
Abstract: Low‐dimensional carbon nanostructures are ideal nanofillers to reinforce the mechanical performance of polymer nanocomposites due to their excellent mechanical properties. Through molecular dynamics simulations, the mechanical performance of poly(vinyl alchohol) (PVA) nanocomposites reinforced with a single‐layer diamond – diamane is investigated. It is found the PVA/diamane exhibits similar interfacial strengths and pull‐out characteristics with the PVA/bilayer‐graphene counterpart. Specifically, when the nanofiller is fully embedded in the nanocomposite, it is unable to deform simultaneously with the PVA matrix due to the weak interfacial load transfer efficiency, thus the enhancement effect is not significant. In comparison, diamane can effectively promote the tensile properties of the nanocomposite when it has a laminated structure as it deforms simultaneously with the matrix. With this configuration, the interlayer sp 3 bonds endows diamane with a much higher resistance under compression and shear tests, thus the nanocomposite can reach very high compressive and shear stress. Overall, enhancement on the mechanical interlocking at the interface as triggered by surface functionalization is only effective for the fully embedded nanofiller. This work provides a fundamental understanding of the mechanical properties of PVA nanocomposites reinforced by diamane, which can shed lights on the design and preparation of next generation high‐performance nanocomposites. Abstract : Atomistic simulations show that 2D diamane can effectively enhance the tensile, compressive, and shear properties of poly (vinyl alchohol) nanocomposite, especially when the nanofiller is laminated with the polymer matrix.